ANALISIS PERSEPSI MANFAAT DAN KEMUDAHAN PENGGUNAAN TERHADAP MINAT DAN ADOPSI INTERNET BANKING PADA PT. BANK RAKYAT INDONESIA (PERSERO) Tbk, CABANG PANGKALAN KERINCI - Febrima, Nade; Zulkarnain, Zulkarnain (Jurnal Tepak Manajemen Bisnis, 2019)
Generally, the national economy is facing a tough challenge, globaleconomic conditions are less favorable lead to higher competition led in thedevelopment of banking sectors. To be a winner in business competition, bankmust have a innovation.This research aimed to analyze the effect of perceivedusefulness and easy of use on intention and adoptionof internet banking towardcustomers in PT. Bank Rakyat Indonesia (Persero) Tbk, Pangkalan KerinciBranch. The research was conducted quantitatively with causal and descriptiveresearch design. The amounts of sample are 100 customers by using proportionalstratified random sampling method. Data collection techniques used in thisresearch is a survey and observation. Measurement scale used is the Likert scale.The data analysis technique used is the analysis of Partial Least Square (PLS)with SmartPLS 3.2.3 applications.The results showed that perceived usefulnes andeasy of use affect significantly positive toward intention but not to adoption. Whilecustomer’s intention of usage has a significant and positive affect toward adoption of internet banking